IMPLEMENTASI PENDEKATAN TaRL BERBASIS METODE PEMBELAJARAN FUN TEACHING UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK - Sofiatul Mu'awanah; Rois Mahfud Setiawan; Rini Indayani; Titis Dwi Hidayati; Rizqi Id-hul Fitri; Ryant Abdillah Dewi P; Arif Mahya Fanny; Ratnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to implement the TaRL approach with the Fun Tecahing method to increase the learning activeness of students at SDN Sumur Welut III Surabaya. This type of research is Classroom Action Research developed by Kemmis and Mc Taggart which includes three stages namely; 1) planning (plan), 2) implementation and observation (act and observe), and 3) reflection (reflect). This research was conducted at SDN Sumur Welut III Surabaya. The subjects of this research were students of class IV-A as many as 28 people. The data collection techniques used were observation and documentation with research instruments in the form of rubrics and observation sheets of students' learning activeness. The results of this study indicate an increase in the learning activeness of students through the implementation of the TaRL approach with the Fun Teaching Method. This can be seen from the results of pre-cycle observations with a percentage of 52.38% in the less active category which then increased by 61.16% in the moderately active category after applying the TaRL approach in cycle 1. Furthermore, it increased again in cycle 2 with a percentage of 80.65% in the active category after applying the TaRL approach with the Fun Teaching method in the learning process. This research proves that the implementation of the TaRL approach with the Fun Teaching method can increase the learning activeness of students in class IV-A SDN Sumur Welut III Surabaya.